Preliminary investigation of emission characteristics of shaving from three wood species utilized for furniture production in Ibadan, Oyo State (2012)
Carpentry workshop is among the prominent and active components of the Nigerian wood industrial sector. The activity in carpentry workshop inevitably generates different categories of wastes. Shavings is among the wood wastes generated in large quantity and the common means of disposing it in major town like Ibadan in Oyo State is by combusting. Large percentage often finds its way to household where it's often used to subsidize fuel for domestic cooking. However, this means of disposal may be prone to health hazard due to the emission released during its combustion. This work examines the combustion characteristics of three typical wood species that are commonly use for furniture production in Ibadan, Oyo state. The species were combusted in Bubbling Fluidized Bed (BFB) combustion under various operating conditions. The result shows that Carbon monoxide (CO) emission is pronounced in the combustion of all the wood species. In all the three cases, Milicia excelsa (Iroko) and Tectona grandis (Teak) have the lowest and highest CO emission respectively. It is suggested that if this waste must be used as fuel for domestic cooking, appropriate technology must be employed especially where low combustion temperature is desirable. However, proper disposition of this waste should be encouraged.